Edukasi Bahaya Gizi Buruk pada Anak dan Penerapan Inovasi Puding Kelor Sebagai Produk Pangan Bergizi dan Peluang Wirausaha di Kelurahan Naikolan Kecamatan Maulafa : Penelitian - Nurina, Rr. Listyawati; Purnasari, Cahyani; Permatasari, Rr. Lilis Intan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to improve family nutritional literacy while presenting nutritious food innovations based on Moringa (Moringa oleifera) through educational activities on the dangers of malnutrition and training in the production of Moringa pudding for mothers of the Family Empowerment and Welfare Movement Team (PKK) in Naikolan Village, Maulafa District, Kupang City. Using a quasi-experimental design with one group pre- and post-activity, nutritional knowledge was measured through pre- and post-tests, while product acceptance was evaluated through a Likert-scale organoleptic test. The results showed an increase in the average knowledge score from 7.24 to 8.40, without a decrease in scores across all participants; the “Good” category increased from 36% to 80%. The organoleptic test on 24 panelists resulted in very high scores for all attributes (color 5.00; aroma 4.70; taste 4.78; texture 4.74; overall 4.87), with 100% of panelists stating “like–really like”. These findings confirm that the combination of nutrition education and moringa pudding innovation effectively increases understanding while producing a product that is well-liked, thus potentially becoming a child-friendly supplementary food solution and a community-based micro-entrepreneurship opportunity.